The Antitumor Effect of Gene-Engineered Exosomes in the Treatment of Brain Metastasis of Breast Cancer - Liu, Minchen; Hu, Yulan; Chen, Guiqian (Frontiers in Oncology, 2020)
Strategies for treating brain metastases of breast cancer have demonstrated limited efficacy due to the blood–brain barrier (BBB). Gene therapy could improve the efficacy of chemotherapeutic drugs. Exosomes derived from the mesenchymal stem cells (MSCs) are small membrane-based gene vectors that can pass through the BBB. CXCR4 is the most commonly found chemokine receptor in human cancer cells. Furthermore, the SDF-1/CXCR4 axis plays an important role in the homing of MSCs for tumor cell diffusion and metastasis. TRAIL can selectively induce apoptosis in transformed cells without significant toxic side effects in normal tissues. In this study, exosomes were isolated from MSCCXCR4+TRAIL transduced with CXCR4 and TRAIL using a lentiviral vector. Synergistic antitumor study showed that exosomeCXCR4+TRAIL exerted significant activity as a cooperative agent with carboplatin in an MDA-MB-231Br SCID mouse model, potentially engendering a novel strategy for advancing the treatment of brain metastases of breast cancer. Based on this study, further investigation of the effect of the vector on BBB and inducing apoptosis of brain tumors is warranted. In addition, the safety of the vector in animals during the treatment needs to be evaluated.